Tratamiento físico químico del agua para el enfriamiento de motores en la generación de electricidad - Acosta-Nardin, Viviana (2022)
This article covers a bibliographic review on the chemical treatment of water, used for the cooling of internal combustion engines, in generating sets. The text includes concepts associated with the generation distributed, cooling systems and their characteristics, the main problems caused by water in the cooling system, corrosion and how to prevent it with the use of inhibitors and different chemical treatments to condition the water, including reverse osmosis.